Pengaruh Fraud Factors terhadap Financial Restatement dan Konsekuensinya terhadap Firm Value - Shafa Salsabila; Yuztitya Asmaranti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Financial statement restatements often negatively impact investor perceptions and a company's market value. Previous studies have shown that companies conducting restatements experience significant share price declines, with an average decline of 20% following the announcement. This phenomenon reflects investors' high sensitivity to negative information related to the reliability of financial statements and suggests that a company's reputation can be damaged quickly. Financial statement restatements are generally associated with material errors or manipulation of financial information, and are therefore often linked to indications of fraud or deception in prior financial reporting. This study aims to analyze the factors influencing financial statement restatements and their impact on firm value, focusing on infrastructure companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research method used is a quantitative approach with secondary data obtained from financial statements and official company publications. The analysis was conducted using logistic regression to examine the influence of fraud factors (pressure, opportunity, and rationalization) on restatements, and linear regression to assess the impact of restatements on firm value. The results of the study indicate that of the three main factors of fraud, only rationalization significantly influences financial statement restatements. Meanwhile, pressure and opportunity do not show significant effects. Furthermore, financial statement restatements were not shown to significantly impact the value of companies in the infrastructure sector during the study period. These findings provide important insights for stakeholders in understanding financial reporting risks and the urgency of strengthening ethics and internal controls in companies.